Case report: epipericardial fat necrosis—a rare cause of chest pain. Issue 1 (31st December 2021) - van den Heuvel, Frederik M A; Dimitriu-Leen, Aukelien C; Habets, Jesse; Nijveldt, Robin
Abstract: Background: Epipericardial fat necrosis (EFN) is a rare cause of chest pain, which is often unrecognized. Case summary: A 58-year-old man previously known with a transient ischaemic attack presented with a sharp, substernal chest pain. Pulmonary embolism was ruled out by computed tomography (CT) angiography. However, CT angiography revealed an inhomogeneous epipericardial mass. On cardiovascular magnetic resonance imaging, the mass had an inhomogeneous signal intensity without infiltration of surrounding tissue. Late gadolinium enhancement imaging showed subtle hyperenhancement. Tissue characterization by means of parametric mapping revealed very low native T1 relaxation times and increased T2 relaxation times. In conclusion, the epipericardial mass showed fibrofatty inflammatory markers, suggestive of EFN. The chest pain resolved spontaneously. Follow-up CT 3 months later showed a marked regression of the mass which confirmed the diagnosis EFN. Discussion: Epipericardial fat necrosis is a benign and self-limiting inflammatory cause of chest pain, which can be diagnosed with multi-modality imaging and must not be overlooked in the differential diagnosis of patients with acute pleuritic chest pain.